(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
Our world is witnessing a great increase in dependence on digital technology, especially with the beginning of the 21st century, where a new reality of services has emerged thanks to what has been made available by the World Wide Web. The latter provided interactive participatory services with very modern electronic templates, by passing the traditional methods that are constantly fading, leaving room for faster and better digital technology in type, sound and image. It soon took over the minds of individuals and paralyzed their thinking to the point of obsession and addiction. The transformation from the traditional addiction, which is based on the use of drugs of all kinds, including opium, heroin, and cocaine, to an addiction and a drug that is more deadly and dangerous. The digital addiction baffled specialists and educators, who are often looking for the best way to save the fragile group of children. Children or teenagers from this new drug, what is the truth about this addiction? From here, we will try in this research paper to shed light on the phenomenon of digital addiction among young people, with the aim of identifying it and highlighting its most important motives and the effects it has on children and adolescents in particular.